APPLYING SHADOWING TECHNIQUE TO IMPROVE STUDENTS’ LISTENING ACHIEVEMENT - Fitri Maini; Rachmanita (Language and Education Journal, 2020)
This study tried find the students’ improvement in listening achievement after having taught by using the shadowing technique. The method used was a quasi-experimental that involved two groups, namely the control group and experimental group. The population of this study was all the tenth graders of SMA Negeri 3 Unggulan Kayuagung with a total number of 198 tenth graders. Purposive sampling method was applied to select the sample involved 72 tenth graders. In collecting the data, try out the test was used to get the desirable questions that would be used in the pretest and posttest to both groups in the control and experimental group. To verify the hypothesis, the normality and homogeneity of the data were firstly analyzed before being continued to be analyzed by using a t-test. Based on the result of data analysis in an independent sample t-test, there were some findings found. First, the mean score of a posttest (75.56) in the experimental group was higher than the pretest (69.03) in the control group. Secondly, the value of tobtained was 2.77 at the significant level of p<0.05 in two-tailed testing with df = 70, the critical value of ttable was 1.99. Since the value of tobtained was higher than ttable, the null hypothesis (Ho) was rejected and the research hypothesis was accepted. In conclusion, it showed that the shadowing technique could improve the tenth-grade students’ listening achievement at SMA Negeri 3 Unggulan Kayuagung